(untitled) (Eduscotech, 2024)
This research aims to determine whether Google Translate influences students’ writing skills, whether the amount of vocabulary known affects their writing skills, and whether Google Translate and vocabulary mastery simultaneously influence students’ writing performance. The research employed a quantitative method. The sample consisted of 29 students from Class 8A of SMPN 1 Maospati, Magetan. Data were collected through a quasi-experimental design using pretest and posttest procedures. Simple linear regression and multiple linear regression analyses were applied to analyze the data. The results indicate that Google Translate significantly influences students’ writing skills, with a significance value of 0.004. Vocabulary mastery also significantly affects students’ writing skills, with a significance value of 0.000. Furthermore, the combined influence of Google Translate usage and vocabulary mastery on students’ writing abilities is significant, with significance values of 0.021 and <0.001, respectively.